Proposed Amendments to the Legal Proposition on Establishment of Non-Marital Paternity from 1855 - Kulauzov, Maša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Proposed amendments to the article 130 of Serbian Civil Code (henceforth: SCC) of 1844 regarding establishment of non-marital paternity were scrutinized in this paper. Originally, establishment of non-marital paternity was granted, but with significant restriction that presumed parent could have been declared the father of an illegitimate child only if he had recognized paternity. That is the reason why in 1855 the Supreme Court suggested amendment to the provision concerning determination of paternity. According to proposed modification, evidence that presumed father was on intimate terms with child᾿s mother in the time of conception should have been sufficient for establishment of paternity. As non-marital relationships were condemned in patriarchal Serbian 19th century society, illegitimate children were considered a product of sin and family disgrace. Hence, the Ministry of Justice, the State Council and Prince Aleksandar Karađorđević were not interested in bettering their position by widening possibilities of determination of fatherhood. Subsequently, in 1868 the amendment was passed by which non-marital paternity could not have been established by a court order, subject to certain exceptions (if one raped or abducted a woman, and the time of conception coincided with the time of abduction or rape). Since 1868 paternity could have been determined solely subject to the consent, i.e. recognition of the illegitimate father.